Upgrading Kompetensi Mengajar Ustadz/Ustadzah untuk Meningkatkan Prestasi Belajar Santri Pondok Pesantren Modern Muhammadiyah Pakusari Kabupaten Jember - Rusdiyanto Rusdiyanto; Ahmad Nur Mahfudza; Isna Nurul Inayati (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Islamic boarding schools developed by the Muhammadiyah organization have modern characteristics, where the learning model used is more in line with the latest learning developments. Facts in the field show that in the modern Pakusari Islamic boarding school still uses traditional methods in learning. for that it is necessary to carry out an upgrading activity of teacher competencies in the Islamic boarding school in order to update the learning method by referring to the current relevant learning model. The method of implementing this community service program is carried out by referring to several stages. Each stage is designed to provide solutions to partner problems. The activity begins with several stages including; Preparation Stage, Implementation Stage, Monitoring and Evaluation Stage, Closing Stage and Follow-up. The results of this Community service activity include; for Learning the yellow book. Application of the Lecture Method, namely the teacher reads, interprets and explains to the students the material being taught. Learning to memorize the Qur'an using the wahdah method, namely memorizing one by one the verses to be memorized. Classroom learning is carried out using the Contextual Teaching Learning (CTL), Discovery Learning, Inquiry, Card Sort, Problem Based Learning (PBL), Cooperative Learning, Index Card Match methods.